Ultrasound-Guided Percutaneous Fasciotomies for Patients With Chronic Exertional Compartment Syndrome - Axel Machado, M.D.; Tristan Fauchille, M.D.; Rayan Fairag, M.D.; Jonathan Cornacchini, M.D.; Nicolas Bronsard, M.D., Ph.D.; Nicolas Ciais, M.D.; Jean-François Gonzalez, M.D., Ph.D.; Alexandre Rudel, M.D.; Grégoire Micicoi, M.D., Ph.D. (Arthroscopy Techniques)
Chronic exertional compartment syndrome is a well-described potential cause of leg pain in high-level athletes and soldiers. Surgical treatment of chronic exertional compartment syndrome usually involves fasciotomy, with a reported rate of complications of up to 16%, including failure of complete compartmental release and delayed return to normal daily activity, which can take up to 6 to 12 weeks. The use of a minimally invasive approach under ultrasound guidance seems to improve clinical outcomes in young active patients. We recommend the following steps for effective execution of ultrasound-guided percutaneous fasciotomy: (1) location of the compartmental fascia and identification of the superficial peroneal nerve, (2) skin incision, (3) insertion of a hook under the compartmental fascia, and (4) sectioning of the fascia.